El proceso de descentralización fiscal en Colombia (2013)
The process of fiscal decentralization in Colombia has experienced an intense structural transformation in recent decades. As a result, the country’s municipalities have received a significant amount of resources from the funding of the powers conferred by the nation, which have been able to meet their capital expenditure, and even part of their operation. Nevertheless, recent reforms passed over their instruments raise questions with the consolidation process.